PENGARUH MODEL PEMBELAJARAN QUANTUM LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA: (Penelitiann Quasi Eksperimen pada Mata Pelajaran IPA di SDIT PERSIS 99 Rancabango) - Mutia Rahmani, Ajeng; Nadiroti Muslihah, Neni (Bale Aksara, 2020)
This research is entitled "The influence of Quantum Learning Models on Students Critical Thinking Ability. The problem in this research is the ability of students' critical thinking in the learning process is low, especially on science subjects in IV grade of SDIT PERSIS 99 Rancabango. It's caused by conventional learning that makes class become static and monotonous so that students aren't trained to solve a contextual question, requires reasoning, argumentation and creativity in completing it. Thís research aims to find out the influence of Quantum Learning model on students critical thinking skills of science learning in IV grade.The research used method of Quasi Experiment with Nonequivalent Control Group Design. The sampling technique in this research is Total Sampling, which is the entire population used as a sample in research with class IVA as a control group with 25 students and class IVB as an experimental group with 25 students, so the total sample in this research amounted to 50 students. The instrument used in this research are test, it is multiple choice questions and description questions. The Technical analysis in this research used t-test to find out whether the Quantum Learning model of learning influences students' critical thinking abilities. The results showed the Quantum Learning model of learning had a significant influence on students' critical thinking skills in Natural Sciences subject of IV grade in SDIT PERSIS 99 Rancabango on the subject of Conservation of Natural Resources and the environment. This is based on the result of calculate data from both of group class, there are differences in the price of tcount with ttable, where tcount> ttable or 6.37> 2.02. So it can be concluded that the application of the Quantum Learning model can influence students' critical thinking skills in the cognitive aspects of science learning of students in fourth grade of SDIT persis 99 Rancabango